Impact of Interest Rates on Consumption in the US Economy: An Empirical Analysis - Katie Ann Dinsdale; Aleksandar Vasilev (The IUP Journal of Applied Finance, 2025)
This study assesses the impact of interest rates on consumption, focusing on how changes in the housing and financial markets implicate consumer spending habits. It addresses how interest rates alter foreign consumption, therefore how imports implicate the consumption of domestic products. While the initial results were not statistically significant, further analysis showed how interest rates have only a limited and weak effect on controlling consumption. However, housing and financial variables did influence consumption, particularly durable goods. The study concludes that monetary policy is ineffective and suggests that the US government explore alternative policies. Further research is warranted to assess the long-term effects on other variables on consumption.
Keywords: E20; 330; interest rates; consumption